2022
DOI: 10.1146/annurev-publhealth-052620-103633
|View full text |Cite
|
Sign up to set email alerts
|

The Indian Health Service and American Indian/Alaska Native Health Outcomes

Abstract: The Indian Health Service (IHS) has made huge strides in narrowing health disparities between American Indian and Alaska Native (AI/AN) populations and other racial and ethnic groups. Yet, health disparities experienced by AI/AN people persist, with deep historical roots combined with present-day challenges. Here we review the history of the IHS from colonization to the present-day system, highlight persistent disparities in AI/AN health and health care, and discuss six key present-day challenges: inadequate f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 74 publications
0
40
0
Order By: Relevance
“…In particular, culturally tailored treatment regimens based in Indigenous systems of knowledge show promising evidence related to improved SUD outcomes (Brave Heart et al , 2011; Hartmann et al , 2019). However, health systems that service Indigenous groups can be poorly resourced (Kruse et al , 2022) and are sometimes located in areas that are geographically removed from the Indigenous populations they intend to serve (Indian Health Service, 2018). There is little catalogued information about the characteristics of culturally tailored programming; how these programs are distributed across tribal, rural and urban Indigenous groups; and what types of substances these interventions address.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, culturally tailored treatment regimens based in Indigenous systems of knowledge show promising evidence related to improved SUD outcomes (Brave Heart et al , 2011; Hartmann et al , 2019). However, health systems that service Indigenous groups can be poorly resourced (Kruse et al , 2022) and are sometimes located in areas that are geographically removed from the Indigenous populations they intend to serve (Indian Health Service, 2018). There is little catalogued information about the characteristics of culturally tailored programming; how these programs are distributed across tribal, rural and urban Indigenous groups; and what types of substances these interventions address.…”
Section: Introductionmentioning
confidence: 99%
“…The focus on neighborhood deprivation is particularly important given the historic nature of federal and state policies that have led to profound levels of racial residential segregation in the United States. For instance, in our cohort racial and ethnic minorities were more likely to live in the most deprived neighborhoods reflecting the longstanding effects of historic policies allowing for redlining, housing discrimination, disinvestment in communities, tribal lands, and Indian reservations 33–35. Therefore, policy efforts to target individual’s living in the most deprived neighborhoods may also aid in the goal of improving cancer care for racial and ethnic minorities.…”
Section: Discussionmentioning
confidence: 84%
“…For instance, in our cohort racial and ethnic minorities were more likely to live in the most deprived neighborhoods reflecting the longstanding effects of historic policies allowing for redlining, housing discrimination, disinvestment in communities, tribal lands, and Indian reservations. [33][34][35] Therefore, policy efforts to target individual's living in the most deprived neighborhoods may also aid in the goal of improving cancer care for racial and ethnic minorities. Prior assessments have demonstrated that individuals with higher socioeconomic disadvantage would travel to a more specialized center for cancer care if financial barriers for travel were removed.…”
Section: Discussionmentioning
confidence: 99%
“…In 1921, the US Congress passed the Snyder Act to authorize funding for the “relief of distress and conservation of health” in Indian communities ( 38 , p. 18). After several reorganization attempts, the 1954 Transfer Act assigned to the US Public Health Service the responsibility for AI health services, and the IHS was created ( 26 , 38 ) to provide health care services on or near AI reservations. Today, the IHS provides mainly primary care and some referral care in a system of hospitals, clinics, and health stations located on or near AI/AN reservations.…”
Section: Historical and Political Contexts Of Ai/ansmentioning
confidence: 99%